Legal Implications of Local Legal Products Formed Without a Problem Inventory List (DIM) - Dinda Suryaningsih; Fauzi Syam; Arfa'i Arfa'i (LOCUS MEDIA PUBLISHING, 2026)
This research is motivated by problems within the local legislative system in Indonesia, where the Problem Inventory List (DIM), a crucial quality control instrument at the central level, loses its regulatory footing at the regional level. This study aims to analyze the institutionalization of DIM in lawmaking and the legal implications of its absence in drafting Local Regulations. Employing a normative juridical method with a statutory approach, the results indicate that at the central level, DIM is an imperative requirement regulated hierarchically (Law No. 12/2011, MD3 Law, and DPR RI Regulation No. 2/2020), where its absence automatically halts deliberations. Conversely, a regulatory vacuum exists at the regional level since Government Regulation No. 12/2018 and Minister of Home Affairs Regulation No. 80/2015 do not mandate it. Consequently, while its absence does not formally invalidate Local Regulations, methodologically it eliminates structural discipline during sessions. Implicatively, this absence triggers substantive issues like policy smuggling, redundant terminology, and fragile considerations clauses, leading to massive corrections by central ministries during evaluations and declining legislative functions within the Regional House of Representatives (DPRD).